Library supervision in participating in library accreditation in Magelang City, Indonesia - Suryanto, Suryanto; Wahyuni, Latifah (Universitas Padjadjaran, 2023)
The Library and Archives Office of Magelang City can be said to be successful in supervising 30 libraries in Magelang City, with the result that 19 libraries got a grade of “A” and 11 libraries got a grade of “B”. It was interesting to study their activities in supervising the libraries in Magelang City. This study aimed to determine how to supervision process was carried out by the Library and Archives Office of Magelang City to supervise libraries in Magelang City that participated in library accreditation. The study used qualitative research with a case study approach conducted in Magelang City. Data collection techniques used interviews with related parties, namely the Library and Archives Office of Magelang City and Library Officers in Magelang City who participated in the accreditation. The selection of informants purposefully used the snowball technique until the data experienced a saturation point. The results showed that the Library and Archives Office of Magelang City carried out supervision consisting of 3 categories: supervising individuals, managing groups, and leading organizations. However, two items were not implemented in supervision activities; the first was managing reward items in the category of supervising individuals. The supervised library considered the accreditation certificate as a reward. The second was budgeting basics items in the category of managing groups. It resulted in the managing reward, which was not implemented; therefore, library supervision has succeed implement the supervision process in participating in library accreditation in Magelang City.